A practical review of alternatives to the steady pressurisation method for determining building airtightness. (October 2020) - Zheng, Xiaofeng; Cooper, Edward; Gillott, Mark; Wood, Christopher
Abstract: As an important indicator of construction quality and envelope integrity of buildings, airtightness is responsible for a considerable amount of energy losses associated with infiltration. It is crucial to understand building airtightness during construction and retrofitting to achieve a suitable envelope airtightness which is essential for obtaining a desirable building energy efficiency, durability and indoor environment. As a convenient means of measurement, the current steady pressurisation method has long been accepted as a standard testing method for measuring building airtightness. It offers an intuitive and robust approach for measuring building airtightness and performing building diagnostics. However, it also has some shortcomings that are mainly related to its high pressure measurement, requirement for skilful operation, long test duration and change to the building envelope. Efforts have been made by manufacturers and researchers to further improve its accuracy and practicality with much progress achieved. Work has also been done to develop alternative methods that can overcome some of the issues. This paper provides a practical review on the incumbent methodology and efforts that have been made over the past decades in research and development of other methods to achieve a similar purpose. It compares them in relation to aspects that are considered important in achieving an accurate, quick and practical measurement of building airtightness and the finding shows other methods such as acoustic and unsteady technique have their own advantages over the steady pressurisation method but also add some of their own restrictions, which therefore makes them suited for different applications. Highlights: This manuscript provides a review on the steady pressurisation. The alternatives to the steady pressurisation method are reviewed and summarised. Reviewed methods are compared with each other from perspectives that are considered important for a practical measurement. Unsteady technique and acoustic method offer advantages but also add some of their own weakness.